Characterization and Classification of Major Mango-Supporting Soils in Semi-arid Ecosystem of South Deccan Plateau, Telangana - K.S. Karthika (Journal of the Indian Society of Soil Science, 2023)
Detailed soil survey was carried out along the major mango-growing areas of three districts of Telangana state experiencing hot moist semi-arid climate, to characterize and classify the soils. Three series were identified namely, Masanpalli series (Siddipet district), Uplingapur series (Medak district), and Dharmapur1 series (Mahabubnagar district). The soils of Masanpalli series were moderately shallow with slightly acidic (pH 6.3), dark brown, loamy sand surface over moderately to slightly acidic (pH 5.7-5.1), reddish brown gravelly clay sub-surface. Uplingapur soils were very deep, moderately acidic (pH 5.9), with subangular blocky structure, and yellowish brown, sandy surface over moderately acidic (pH 5.7), dark red, sandy clay sub-surface. Dharmapur 1 soils were moderately deep, with dark brown, moderately alkaline (pH 7.96), gravelly sandy loam A horizons and dark reddish brown colour, neutral, sandy clay loam to gravelly sandy clay B horizons. Based on USDA soil taxonomy at the family level soils of Masanpalli series were classified as loamy-skeletal, mixed, Typic Haplustalfs, soils of Uplingapur series were classified as fine, kaolinitic, Rhodic Paleustalfs, and soils of Dharmapur 1 series were classified as Clayey-skeletal, mixed, Typic Rhodustalfs. It was observed that strong acidity of soils of Uplingapur series, low organic carbon and gravelliness in soils of Masanpalli and Dharmapur 1 series pose limitation to mango cultivation. Hence, suitable management interventions need to be adopted to improve the production efficiency of mango orchards in the area.